Improving public health competencies through required practice experience. (November 2016) - Steigerwald, D.; Nolan, C.; Loux, T.; Baskin, C.R.; Scharff, D.P.
Highlights: The internship experience improves MPH core competencies. The internship experience improves MPH concentration-specific competencies. The internship is an important part of a competency-based public health education.